2019
DOI: 10.1055/s-0039-1692454
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Relationships between Visceral Fat Measures and Adipokines Concentrations among Women with a History of Preeclampsia

Abstract: Objective We sought to evaluate associations between postpartum plasma adipokine concentrations among women with a history of preeclampsia (PE) without severe features (MPE), PE with severe features (SPE), and no PE (NPE). We also investigated relationships between adipokines and computed tomography (CT)-quantified measures of visceral fat (VF) area (VFA) and subcutaneous fat area (SCFA). Study Design We performed a secondary analysis of data collected as part of a previously performed cross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…Conversely, one case-control study with 117 pregnant women found no significant difference in maternal serum resistin levels between PE patients and healthy controls; however, it reported a positive correlation between serum resistin and subcutaneous fat area in PE women [32]. A secondary analysis of 64 patients who had a history of PE and healthy controls 10 years after delivery found maternal resistin concentrations to be similar among both groups [33].…”
Section: Resistin In Gdm and Pementioning
confidence: 96%
“…Conversely, one case-control study with 117 pregnant women found no significant difference in maternal serum resistin levels between PE patients and healthy controls; however, it reported a positive correlation between serum resistin and subcutaneous fat area in PE women [32]. A secondary analysis of 64 patients who had a history of PE and healthy controls 10 years after delivery found maternal resistin concentrations to be similar among both groups [33].…”
Section: Resistin In Gdm and Pementioning
confidence: 96%
“…Triplane tissue Doppler imaging (TDI) has fast imaging speed and high image resolution and overcomes the interference of respiratory motion [ 9 ]. Nowadays, triplane TDI has been widely used in the diagnosis of congenital heart diseases, pulmonary embolism, pulmonary hypertension, and other diseases [ 10 ].…”
Section: Introductionmentioning
confidence: 99%